Tax optimization management in the context of shadow economy performance - Andrzej Buszko; Anna Firkowska (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2025)
The article is devoted to tax optimization in the relation do shadow economy performance. The importance of rule 2018/822 issued by ECOFIN has been  highlighted. The characteristic finance transactions have been   clarified providing the impact for tax optimization enlargement. The close attention was paid to the benefits due to the fact of minimization of tax obligations.